Do personality traits have an impact on anxiety levels of athletes during the COVID-19 pandemic? - (:unkn) unknown (TERMEDIA PUBLISHING HOUSE LTD, 2021)
BACKGROUND The sports world is one of the sectors most affected by the SARS-CoV-2 (COVID-19) pandemic. Athletes from specific sport disciplines have experienced the new situation in different ways. Therefore, understanding their individual experiences and psychological responses may help to design better intervention programs. Accordingly, this study investigated the relationship between athletes' personality traits and anxiety in the light of their individual experiences during the COVID-19 pandemic. PARTICIPANTS AND PROCEDURE The COVID-19 impact questionnaire, Big Five Inventory-35, and the State-Trait Anxiety Inventory were administered to 321 male and 168 female athletes in Turkey from various sport disciplines. At the time of data collection, training and competitions had been canceled in all sports for two months. RESULTS Most athletes (70.7%) were worried about being infected with SARS-CoV-2 if competitions were to restart soon. The regression analyses revealed that emotional stability, extroversion, and age were negative predictors of state anxiety; emotional stability, extroversion, and conscientiousness were negative predictors of trait anxiety; agreeableness was a positive predictor of state anxiety. Athletes who perceived that their relationships with family or close friends worsened during home confinement (17.2%) had significantly higher state anxiety and trait anxiety scores than those who perceived a positive relationship change (28%) or no relationship change (54.8%). The agreeableness, conscientiousness, and emotional stability scores of athletes who perceived a negative relationship change with family or close friends were also significantly lower than for athletes who perceived no change or a positive change. CONCLUSIONS Overall, personality traits affected athletes' anxiety levels and their relationships during the COVID-19 pandemic.
Keywords: sport; trait anxiety; coronavirus; state anxiety; Big Five personality traits; STRESS; SPORT